Volume 2C: Turbomachinery 2014
DOI: 10.1115/gt2014-25759
|View full text |Cite
|
Sign up to set email alerts
|

Study of Particle Ingestion Through Two-Stage Gas Turbine

Abstract: This paper presents a numerical study of particle laden gas flow through a two-stage hp axial turbine, by means of an inhouse code based on the Lagrangian tracking model and the finite element method. As fly-ash solid particles trajectories and locations of impacts are predicted, the local erosion rates and the deteriorations of blades are assessed. The computed trajectories provide a detailed description of particles behaviors and reveal that particle impacts on the aft of vane pressure side usually lead to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…It was found that the blade tip region was especially susceptible to erosion, and particles were observed to have multiple impacts on both the rotor and stator. Ghenaiet [7] studied erosion in a two-stage gas turbine using a frozen-rotor multiple reference frame model. The injected particles ranged from 1 to 150 lm, and were found to impact the trailing portion of vanes and leading edge region of rotor blades in each stage.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the blade tip region was especially susceptible to erosion, and particles were observed to have multiple impacts on both the rotor and stator. Ghenaiet [7] studied erosion in a two-stage gas turbine using a frozen-rotor multiple reference frame model. The injected particles ranged from 1 to 150 lm, and were found to impact the trailing portion of vanes and leading edge region of rotor blades in each stage.…”
Section: Introductionmentioning
confidence: 99%
“…The methodology adopted here for analyzing particle ingestion in an axial compressor stage is different from that reported in the literature [9][10][11][12][13][14]. In this case, in fact, particles are not tracked through the interface between rotating and stationary domains, but the analysis is carried out by means of separate particle injections for the isolated rotor and stator cascades.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent work, 117 Zagnoli et al [9] report a review of the computational studies per-118 formed in past years tracking different types of particles through 119 compressor and turbine stages. In these works, most of which deal 120 with erosion in compressors [10,11] and turbines [12][13][14], and 121 steady (mixing plane and frozen rotor) and unsteady models are 122 employed at the interface between rotating and stationary domains 123 for the rotor/stator coupling. The authors in Ref.…”
mentioning
confidence: 99%
“…For example, Suzuki et al [8] numerically studied sand erosion in an axial compressor stage using an unsteady calculation with temporal grid geometry updates and found that many repeat impacts occur for both rotor and stator blades with the blade tip being the most susceptible to erosion. Ghanaiet [9] numerically studied particle ingestion in a two-stage gas turbine for particles ranging from 1 to 150 μm in size and found that the trailing edge of the pressure surface of first and second stage vanes as well as the leading edges of first and second stage blades were highly susceptible to particle impacts and subsequent erosion. Ghaneiet used a frozen rotor, multiple reference frame model to calculate the interface between stators and rotors.…”
Section: Figure 12: Damage To Turbine Blading Due To Deposition [4]mentioning
confidence: 99%